GUIDELINES FOR THE DEVELOPMENT OF SAFETY IN SCHOOLS UNDER UBONRATCHATHANI PRIMARY EDUCATION SERVICE AREA OFFICE 2 - Prommueang, Anupong; Udorn, Nawee; Buppataweesak, Akkharawat (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The purposes of this research were to 1) examine the current and desired conditions of school safety operations; 2) assess the needs for developing school safety; 3) develop guidelines for developing school safety; and 4) evaluate the appropriateness and feasibility of guidelines for developing safety in schools under Ubonratchathani Primary Educational Service Area Office 2. The sample group consisted of 337 participants, including 26 school administrators and 311 teachers. The research instruments comprised a set of questionnaires, an interview form, and an assessment form regarding feasibility. The percentage criteria were used in determining the sample size. The statistics employed were mean, standard deviation, and the modified priority needs index (PNI Modified). The research results revealed that 1) the overall current conditions regarding guidelines for developing school safety, while the overall desirable conditions were at the highest level; 2) The needs that were higher than the overall average included accident measures, physical and psychological aspects; 3) The guidelines for developing school safety comprised five aspects: (1) accident measures, (2) physical and psychological aspects, (3) school environment (4) violence prevention and (5) disaster management; and 4) The overall developed guidelines were assessed at a high level of appropriateness and feasibility.